Assessment of public welfare in Ukraine in the context of the COVID-19 pandemic and economy digitalization - Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V.; Козловський, Сергій Володимирович; Козловський, С. В.; Козловский, Сергей Владимирович; Kozlovskyi, Serhii V.; Байдала, Вікторія Володимирівна; Байдала, В. В.; Байдала, Виктория Владимировна; et al. (Business Perspectives, 2021)
With the emergence of the global COVID-19 pandemic in 2019, a process of transformation of the modern economic system took place, which requires new approaches to assessing economic processes. One of such processes is the assessment of public welfare. The purpose of this study is to develop an approach to assessing the level of public welfare of the population of Ukraine in the context of the COVID-19 pandemic and economy digitalization. To solve this problem, the methods of artificial intelligence, in particular the method of fuzzy sets theory, which allows using the incomplete information and making high-quality forecast calculations, are used. The factors influencing the level of public welfare during the COVID-19 pandemic have been identified. These are the following factors: gross domestic product, poverty rate, welfare index, human development index, subsistence level, and indicators that characterize the COVID-19 pandemic (i.e. the total number of COVID-19 cases, the total number of deaths from COVID-19, and the total number of vaccinations from COVID-19 in Ukraine). Using fuzzy sets theory, an economic-mathematical model for assessing the level of public welfare in the context of the COVID-19 pandemic in Ukraine was built. Two-dimensional dependences of the level of public welfare of Ukraine in the context of the COVID-19 pandemic on indicators such as gross domestic product, subsistence level, and the total number of cases of COVID-19 in Ukraine were obtained. The results of the study established that the level of public welfare in the context of the COVID-19 pandemic on the 0-100 scale is predicted to be as follows points: 2021 – 17, 2022 – 23, 2023 – 27, 2024 – 19, 2025 – 35 and will not meet international standards.

З появою глобальної пандемії COVID-19 у 2019 році відбувся процес трансформації сучасної економічної системи, що потребує нових підходів до оцінки економічних процесів. Одним із таких процесів є оцінка суспільного добробуту. Метою даного дослідження є розробка підходу до оцінки рівня суспільного добробуту населення України в умовах пандемії COVID-19 та цифровізації економіки. Для вирішення цієї проблеми використовуються методи штучного інтелекту, зокрема метод теорії нечітких множин, що дозволяє використовувати неповну інформацію та робити якісні прогнозні розрахунки. Визначено фактори, що впливають на рівень суспільного добробуту під час пандемії COVID-19. Це такі фактори: валовий внутрішній продукт, рівень бідності, індекс добробуту, індекс людського розвитку, прожитковий мінімум та показники, що характеризують пандемію COVID-19 (тобто загальна кількість випадків COVID-19, загальна кількість смертей від COVID-19) та загальна кількість щеплень від COVID-19 в Україні. Використовуючи теорію нечітких множин, побудовано економіко-математичну модель оцінки рівня суспільного добробуту в умовах пандемії COVID-19 в Україні. Отримано двовимірні залежності рівня суспільного добробуту України в умовах пандемії COVID-19 від таких показників, як валовий внутрішній продукт, прожитковий мінімум та загальна кількість випадків COVID-19 в Україні. За результатами дослідження встановлено, що рівень суспільного добробуту в умовах пандемії COVID-19 за шкалою 0-100 прогнозується за такими балами: 2021 – 17, 2022 – 23, 2023 – 27, 2024 – 19 , 2025 – 35 і не відповідатиме міжнародним стандартам.
Kozlovskyi S. Assessment of public welfare in Ukraine in the context of the COVID-19 pandemic and economy digitalization / S. Kozlovskyi, I. Petrunenko, V. Baidala, V. Myronchuk, T. Kulinich // Management. - Vol. 19. - Issue 1. - - Business Perspectives, 2021. - P. 416 – 431.
Keywords: digital economy; management; economic assessment; welfare; artificial intelligence; fuzzy sets theory; forecasting; цифрова економіка; менеджмент; економічна оцінка; добробут; штучний інтелект; теорія нечітких множин; прогнозування; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics